The effect of resistance exercise on fitness, blood pressure, and blood lipid of hypertensive middle-aged men - Shim, Kyu-Sik (J Exerc Rehabil, 2017)
The purpose of this study is to investigate the effect of resistance exercise on fitness, blood pressure, and blood lipid of hypertensive middle-aged men. To achieve the goal of the study, a total of 23 subjects were selected. Among them, 14 subjects who exercised regularly were selected as the exercise group, while the remaining 9 subjects were selected as the control group. In terms of data processing, the IBM SPSS Statistics ver. 21.0 software was used to calculate the mean and standard deviation. Regarding the verification of difference on the change of means between the groups, analysis of covariance was used for statistical process. As a result, significant differences were found in cardiovascular endurance, muscle endurance, flexibility, and triglyceride. These results indicate that the resistance exercise only had slight effect on hypertensive middle-aged men.